Can the dermatitis from the hot spot be minimised by barrier film? - Lim, Fiona; Wan, Bo Angela; Razvi, Yasmeen; Chow, Edward (Therapeutic Radiology and Oncology, 2018)
Breast conservative surgery followed by radiotherapy has been increasingly used for treating breast cancer, particularly for those with early stage disease to allow organ preservation while maintaining similar oncological outcomes when compared to mastectomy (1,2). Traditional radiotherapy in such settings includes treating the whole breast in conventional fractionation of 2 Gray (Gy) per fraction to total 25 fractions over 5 weeks, with or without boost to the tumor bed to further decrease local recurrence (3,4).